Environmentally Caring Characters in Students Through Animated Videos Assisted by the Canva Application - Nurulaeni, Fitria; Suhada, N. Nurhaliza (Journal of Innovative Science Education, 2024)
Although students' understanding of environmental protection still needs to improve, increasing their awareness of the environment is very important because environmental problems are becoming increasingly complex. Through a discussion of living things, this research aims to determine the differences in the environmentally caring character of students in the experimental class and control classes. The research used was an experiment with a quasi-experimental type (posttest-only control design). Questionnaires and observations were used as data instruments, using an experimental class of 27 students and 21 students for the control class. The Mann-Whitney test is the data analysis method used.  The research results showed that the average value of experimental class data was 29.06 higher than that of control class data 18.64. In addition, the asymptotic sig value (2-tailed) of 0.010 < 0.05 was calculated based on the results of the Mann-Whitney test, indicating that the experimental class and the control class were different in their environmental care attitudes. Based on these findings, using animated videos with the help of Canva can attract attention and spark children's imagination. After watching animated videos, children can act according to what they learn and digest information easily on what they observe in animated video shows.